2019
DOI: 10.1038/s41467-019-10065-8
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous GM-CSF signaling in macrophages is associated with control of Mycobacterium tuberculosis

Abstract: Variability in bacterial sterilization is a key feature of Mycobacterium tuberculosis (Mtb) disease. In a population of human macrophages, there are macrophages that restrict Mtb growth and those that do not. However, the sources of heterogeneity in macrophage state during Mtb infection are poorly understood. Here, we perform RNAseq on restrictive and permissive macrophages and reveal that the expression of genes involved in GM-CSF signaling discriminates between the two subpopulations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 39 publications
2
61
0
Order By: Relevance
“…GM-CSF has been increasingly appreciated as an essential mediator of protective immunity against TB 25 31 . However, the mechanisms underlying the pathology observed in the absence of GM-CSF signalling during M. tuberculosis infection remain poorly understood, particularly since past studies performed in GM-CSF-deficient mice had confounding lung pathologies 33 , 34 , hampering interpretation of the findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GM-CSF has been increasingly appreciated as an essential mediator of protective immunity against TB 25 31 . However, the mechanisms underlying the pathology observed in the absence of GM-CSF signalling during M. tuberculosis infection remain poorly understood, particularly since past studies performed in GM-CSF-deficient mice had confounding lung pathologies 33 , 34 , hampering interpretation of the findings.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages and CD4 + T cells, and several cytokines such as IL-12, IFN-γ, TNF and IL-1 have been shown to play a major role in protection against M. tuberculosis infection 2 4 , 13 , 21 24 . More recently, GM-CSF has also been increasingly recognised as a key mediator for TB resistance 25 31 , and is in the pipeline for host-directed therapy as an adjuvant treatment of TB 32 . The presence of GM-CSF specific autoantibodies that block GM-CSF function have been linked to cryptococcal disease and some cases of pulmonary TB 28 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in mice show that deficiency in GM-CSF results in the inability to contain infection ( Gonzalez-Juarrero et al., 2005 ). Other research suggests that survival of bacteria in macrophages is regulated by GM-CSF response in macrophages ( Bryson et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies that have been conducted in murine models of TB suggest that the production of GM-CSF by lung epithelial cells, conventional, and non-conventional T cells are essential for generating a protective immune response and restricting MTB growth in the lungs ( 8 11 ). A recent study, clearly suggested that human macrophages were also able to produce GM-CSF upon infection with MTB, and their antimycobacterial properties correlated with their ability to produce GM-CSF ( 12 ). While MTB-infected human macrophages displayed cell-to-cell variability in their antibacterial capacity, cell populations with increased expression of genes involved in the GM-CSF signaling pathway were able to better control MTB growth.…”
mentioning
confidence: 99%